Interclonal gradient of virulence in the Pseudomonas aeruginosa pangenome from disease and environment. (29th September 2014) - Hilker, Rolf; Munder, Antje; Klockgether, Jens; Losada, Patricia Moran; Chouvarine, Philippe; Cramer, Nina; Davenport, Colin F.; Dethlefsen, Sarah; Fischer, Sebastian; Peng, Huiming; Schönfelder, Torben; Türk, Oliver; et al.
Summary The population genomics of Pseudomonas aeruginosa was analysed by genome sequencing of representative strains of the 15 most frequent clonal complexes in the P. aeruginosa population and of the five most common clones from the environment of which so far no isolate from a human infection has been detected. Gene annotation identified 5892–7187 open reading frame (ORFs; median 6381 ORFs) in the 20 6.4–7.4 Mbp large genomes. The P. aeruginosa pangenome consists of a conserved core of at least 4000 genes, a combinatorial accessory genome of a further 10 000 genes and 30 000 or more rare genes that are present in only a few strains or clonal complexes. Whole genome comparisons of single nucleotide polymorphism synteny indicated unrestricted gene flow between clonal complexes by recombination. Using standardized acute lettuce, Galleria mellonella and murine airway infection models the full spectrum of possible host responses to P. aeruginosa was observed with the 20 strains ranging from unimpaired health following infection to 100% lethality. Genome comparisons indicate that the differential genetic repertoire of clones maintains a habitat‐independent gradient of virulence in the P. aeruginosa population.